COMPUTATIONAL STUDY WITH DENSITY FUNCTIONAL THEORY APPROACH FOR REACTION MECHAMISM OF CHALCONE-FLAVANONE CONVERSION - Zulaikha Hildayani, Suci
Flavanones are compounds of the flavanoid class which have many benefits, one of them that is very useful in the field of pharmacology as a precursor of drugs. The synthesis of flavanones, both naturally in plants and experimentally in the laboratory, is often carried out by converting chalcone molecule to flavanone. Biosynthetically, the conversion reaction of chalcone into flavanone takes place with the help of the enzyme chalcone isomerase (CHI). This reaction is known to occur in a simple, one-step, and produces enantioselective products. However, the synthesis of flavanone from 2-hydroxy chalcone in the laboratory often results in a racemic product, a mixture of 2S-flavanone and 2R-flavanone. One of the effective methods for converting chalcone into flavanone that has been done by previous researchers is to use methane sulfonic acid as a catalyst. Even though the reaction product is a racemic product, this reaction can take place by producing a good yield. In addition, the methane sulfonic acid catalyst is suitable for green chemistry applications. Other catalysts that have been used to produce enantioselective products are from aminoquinoline and pyrrolidine derivatives. This catalyst is taken from the active site segment of the CHI enzyme. Whether catalyzed by methane sulfonic acid or by aminoquinoline and pyrrolidine derivatives, the mechanism for this reactions are not known with certainty. So the purpose of this research is to study the reaction mechanism for the conversion of chalcones to flavanones with methane sulfonic acid catalyst and aminoquinoline and pyrrolidone derivatives as catalysts. The research method used is quantum computing with density function theory (DFT) at the level of theory and basis sets M06-2X/6-311**(d,p). The results of computational calculations show that the reaction mechanism of the conversion of chalcones into flavanones with methane sulfonic acid catalyst occurs through two steps, namely the cyclization step and the carbonylation step. The reaction mechanism of the conversion of chalcones into flavanones with the catalyst of aminoquinoline and pyrrolidine derivatives takes place through two similar steps, the cyclization and carbonylation steps. The use of asymmetric catalysts derived from aminoquinoline and pyrrolidine can lead to the formation of S-flavanone products by forming ?…?-stacking interaction and hydrogen bonds between the reactants and the catalyst.